Kinerja Keuangan Bank Ditinjau dari Pertumbuhan Aset, Solvabilitas, dan Perputaran Total Aset dengan Risiko Pembiayaan Sebagai Variabel Moderating (Studi Kasus Pada Bank Umum Syariah Periode 2016-2020) - Efi Septiani; Arna Asna Annisa (Islamic Economics and Business Faculty of UIN Antasari, 2021)
This research is motivated by the competitive development of banking in Indonesia which is very tight, so it is expected that Islamic banking has better financial performance so that it can compete with the national banking market. The purpose of this study is to determine the Analysis of the Effect of Asset Growth, Debt To Asset Ratio, and Total Asset Turnover on the Financial Performance of Banks With Non-Performing Financing as Moderating Variables (Case Study of Islamic Commercial Banks Period 2016-2020). Quantitative research is a type of research. Then use Moderate Regression Analysis (MRA) as data analysis and use panel data. A sample of 65 observational data was obtained which was then tested through the E-views 10 application. The results of the research concluded that partially the Asset Growth variable had a positive and insignificant effect on financial performance, Debt To Asset Ratio (DAR) had a positive and insignificant effect on financial performance. , Total Asset Turnover (TATO) has a positive and significant effect on financial performance. Non-Performing Financing is able to moderate the effect of Debt To Asset Ratio (DAR) and Total Asset Turnover (TATO) but is unable to moderate the effect of Asset Growth on financial performance. Penelitian ini dilatarbelakangi oleh persaingan perkembangan perbankan di Indonesia yang sangat ketat, sehingga diharapkan perbankan syariah mempunyai kinerja keuangan yang semakin baik sehingga mampu bersaing dengan pasar perbankan nasional. Tujuan penelitian ini untuk mengetahui Analisis Pengaruh Asset Growth, Debt To Asset Ratio, Dan Total Asset Turnover Terhadap Kinerja Keuangan Bank Dengan Non Performing Financing Sebagai Variabel Moderating (Studi Kasus Bank Umum Syariah Periode 2016-2020). Quantitative research adalah jenis risetnya. Kemudian penggunaan Moderat Regression Analysis (MRA) sebagai data analysis serta memakai data panel. Didapatkan sampel sebanyak 65 data pengamatan selanjutnya diuji melalui aplikasi E-views 10. Hasil riset menyimpulkan bahwa secara parsial variabel Asset Growth memiliki pengaruh yang positif dan tidak signifikan terhadap kinerja keuangan, Debt To Asset Ratio (DAR) berpengaruh positif dan tidak signifikan terhadap kinerja keuangan, Total Asset Turnover (TATO) berpengaruh positif dan signifikan terhadap kinerja keuangan. Non Performing Financing mampu memoderasi pengaruh Debt To Asset Ratio (DAR) dan Total Asset Turnover (TATO) namun tidak mampu memoderasi pengaruh Asset Growth terhadap kinerja keuangan.